3D-printed interdigitated graphene framework as superior support of metal oxide nanostructures for remarkable micro-pseudocapacitors. (1st October 2019) - Wang, Teng; Li, Liang; Tian, Xiaocong; Jin, Hongyun; Tang, Kang; Hou, Shuen; Zhou, Han; Yu, Xianghua
Abstract: Micro-sized electrochemical energy storage device is a prospective candidate to power the miniaturized electronic devices and micro-pseudocapacitor (MPC) is a typical one with high power density and long life span. Developing a versatile architectural design with high capacity delivering in a micrometer range is paramount for remarkable MPC constructions. Here, an interdigitated graphene framework (IGF) is developed using a facile 3D printing technique to enable the customized geometries as well as the superior support of metal oxide nanostructures. With this unique design, the IGF-supported NiO nanorod heterostructured microelectrodes deliver high specific capacity of 220.2 C g −1 (400.3 F g −1 ). When directly assembled to quasi-solid-state symmetric MPCs, the NiO filled one exhibits a remarkable device capacity of 197.5 mC cm −2 . Robust MPC cycling stabilities are also demonstrated during 10000 charge and discharge cycles. In addition to the NiO based ones, MnO2 nanosheet filled MPCs are also fabricated, where a high device capacity and a good cycling stability are also exhibited. We expect that this novel 3D-printed IGF can pave the way for constructing state-of-the-art miniaturized electrochemical energy storage devices with customized geometries. Graphical abstract: Image 1